An axiological study on Islamic visual art in Malaysia from 1957 to 1999 / Wan Samiati Andriana W.Mohamad Daud - W.Mohamad Daud, Wan Samiati Andriana (2017)
The Islamic values were determined from Allah SWT through the Al-Quran and the guidance of the Prophet Muhammad SAW. The aims of this study were to determine the axiological aspect of the Contemporary Malaysian Islamic Visual Art, to explore the historical events and the development of the Malaysian Islamic Art from the year of 1957 to 1999, and to provide a comprehensive document on the history of the Contemporary Malaysian Islamic Visual Art based on history, tradition and culture of Islam. This research was conducted by using mixed methods of qualitative and quantitative research method. The quantitative research utilized questionnaire to solicit the data. The information gathered through data collection inclusive of three major issues, the concept , the national policies and the events or exhibitions gathered from various source s, including academic books , journal, proceedings as well as exhibition catalogues cum books of painting, retrospectives, biographies, competition booklets and website. The important events on Islamic art were also gathered through the articles presented at seminars and symposiums as well as newspaper cuttings and magazines. The study also analysed ninety five (95) pieces of artworks consist of artwork from painting, printmaking, sculpture and mix media such as collages, assemblages, digital print, fabric works and two-dimensional construction that were exhibited in Islamic Art exhibitions held in Malaysia from the years 1957 to 1999 and were selected from those created by the Muslim artists with the Islamic Art themes only. As for the survey, 407 questionnaires were distributed to the UiTM communities through out Malaysia focusing on the view and exposure of Islamic Art, the understanding of the axiology philosophy, the awareness of visual art and the artist artwork. The soliciting process has enabled the researcher to record and organize all important details of each selected sample of artworks, including the name of the artist, the venue of the exhibition, and the date according to the Islamic theme exhibition. Other details of the sample artworks also have been put into consideration and recorded accordingly, such as the artwork's title, dimension or size of the artwork, media and techniques used in produc ing the artwork. The researcher followed the integrative approach and applied the technique of the descriptive quantitative approach and report the summary database on the percentage, to describe, explain and validate the findings. In the assessment of the awareness of the respondents pertaining to visual art, finding reveals that the majority of the respondents has taken art education before were aware of visual art because they have been to an art exhibition and like any exhibited artwork. However, most of the respondents have never heard about the National Cultural Congress (1971). The finding also shows that most Malaysian have never heard of the term 'axiological study' before and does not know about the development of Islamic Art in Malaysia. 71% the respondents believed that the image of the pictures produced by the artists was not an Islamic art and only 29% believed they were Islamic art. This is a clear indication that the Malaysian are lacking in the knowledge pertaining to the Islamic visual art. Hence, it is recommended that further research should review the axiological aspects of visual art in Malaysia and Southeast Asia. The studies on Islamic art and its spiritual message in Malaysian visual art should also be conducted.